Images of Dutchness: Popular Visual Culture, Early Cinema and the Emergence of a National Cliché - Dellmann, Sarah (Framing Film, 2018)
Why do early films present the Netherlands as a country full of canals and windmills, where people wear traditional costumes and wooden shoes, while industries and modern urban life are all but absent? Where do such visual clichés come from? This study investigates the roots of this imagery in popular visual media ranging from magazines to tourist brochures, from anthropological treatises to advertising trade cards, stereoscopic photographs, picture postcards, magic lantern slide sets and films of early cinema. The book provides an in-depth study of this rich and fascinating corpus of popular visual media that has not been studied before, and the discourses that these images were meant to illustrate. This intermedial approach offers new insights into the emergence of national clichés and the study of stereotypical thinking.